How Chinese Enterprises Use Futures and How to Manage Its Risk - Xu, Jia (2007)
Volatility in the prices of primary commodities creates revenue uncertainty for Chinese enterprises. Recent development suggests that the most hopeful solution for Chinese enterprises is the using of futures markets to hedge against adverse prices movement. With the further liberalization and oriented of Chinese economies, more and more Chinese enterprises engaged in futures markets. However, many of them have often committed very basic mistakes in derivatives markets and some of them incurred huge losses. The reason of most of the derivatives disaster cases is not the derivatives trading itself but the lacking of internal control and risk management system. From a case of the China Aviation Oil Singapore Corp Ltd that lost 550 million US dollars in futures speculative trading, one can see that the establishment of a complete and efficient risk control system is necessary for an enterprise to engage in derivatives trading. However, the most important thing is whether the risk control system is severely implemented or not.